PEMERIKSAAN TELUR SOIL TRANSMITTED HELMINTH (STH) PADA KUBIS (BRASSICA OLERACEA) DAN KEMANGI (OCIMUM BASILICUM) DI PASAR TRADISIONAL BEKASI - Reza Anindita; Vincentia Donalda Petra Lerrick; Maulin Inggraini (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Worm infections caused by Soil Transmitted Helminth (STH) in Indonesia cause diarrhea, malnutrition, and malaise. One of the epidemiology of STH occurs through soil or fertilizer contaminated with STH in vegetables. Therefore, it is necessary to examine and identify STH in vegetables, especially cabbage and basil. The purpose of this study was to determine STH eggs in vegetables from cabbage (Brassica oleracea) and basil (Ocimum basilicum) taken at Pasar Baru, Bekasi. This type of research is descriptive and quantitative with a cross-sectional design. The samples in this study were 12 cabbage and 9 basil leaves taken from Pasar Baru, Bekasi. The sampling technique used was purposive sampling. Data analysis was done by quantitative descriptive. The results of this study showed that 3 (25%) samples of cabbage and 3 (22.22%) of basil were found to be positive for the presence of STH eggs. The species of STH eggs that were identified were fertile and non-fertile Ascaris lumbricoides. This study concluded that there was contamination of fertile and non-fertile A. lumbrocoides eggs in cabbage and basil vegetables sold in Pasar Baru, Bekasi.Keywords: STH eggs, basil, cabbage, Ascaris lumbricoides, sedimentation method